Protein Corona: Impact of Lymph Versus Blood in a Complex In Vitro Environment. Issue 29 (5th June 2017) - Bonvin, Debora; Aschauer, Ulrich; Alexander, Duncan T. L.; Chiappe, Diego; Moniatte, Marc; Hofmann, Heinrich; Mionić Ebersold, Marijana
Abstract : In biological environments, the surface of nanoparticles (NPs) are modified by protein corona (PC) that determines their biological behavior. Unfortunately, in vitro tests still give different PC than in vivo tests causing in vitro–in vivo discrepancy; hence, in vitro studies are not indicative for the NPs' behavior in vivo. Here is demonstrated that PC in vitro is strongly influenced by the type of extracellular fluid (ECF), blood or lymph, by their high and low flow conditions and transitions between ECFs, and a combination of these parameters. As a result, this in vitro study approaches fluidic and dynamic variations to which NPs are exposed in vivo: different ECF that NPs encounter first in different injection routes, different transitions in‐between ECFs during circulation, and simultaneous change in the exposed flow in these transitions. The most‐abundant proteins in PCs are found to be not the most abundant in ECFs, but those having high affinity for binding to the surface of NPs. Moreover, some proteins are differently abundant in PCs at different flows, which indicate force‐promoted binding, catch bonds. These results suggest that future in vitro studies should consider more complex incubation conditions to improve the in vitro–in vivo consistency necessary for translational research. Abstract : Protein corona of lymph versus blood under different flow conditions, and transition from one extracellular fluid to another are studied. Simultaneous inclusion of these novel parameters leads to dramatic changes in the protein corona. Preferentially bound proteins are rich in chemical groups with high affinities for binding to the surface of nanoparticles.